Membangun Rumah Tuhan: (EZRA 3: 8-13) - Dea Purba; Gusti Sihombing; Pinondang SumanSimanjuntak (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
Ezra means helper. Ezra was a prophet sent by God to lead the Israelites after the exile. After the exile ended, the Israelites intended to build a temple for God. They face many challenges and obstacles, but when God is with them everything can be overcome easily. Just like us today, when we surrender to God everything we want, God will suffice. Just as in building God's house of worship, the Israelites were so enthusiastic when they wanted to build God's house, we too as God's congregation should have the same commitment as the Israelites in building God's house. Because that is one form in which we glorify God and how we give what is best for God. We must emulate the Israelites with great enthusiasm. When they laid the first stone in the construction of God's house, they were very happy, they praised God, sang and played musical instruments such as the harp, ciracap and also the trumpet. Even among all the shouts of cheers and songs of joy, there were also those among them who were crying, moved by what they had been through so far. Such great enthusiasm enabled the Israeli people to do this and overcome all the challenges in their lives.